Thermal Performance Evaluation and Testing of Improved Animal Feed Solar Cooker - Poonia, Surendra; Singh, A. K.; Santra, P.; Nahar, N. M.; Mishra, D. (Journal of Agricultural Engineering, 2017)
An improved solar cooker for animal feed was fabricated using locally available materials as bricks, cement, sand and pearl millet hull. The commercial materials used for its fabrication were glass covers, 24 SWG galvanised steel, wood, aluminum sheet, and cooking utensils. Length to width ratio of the cooker was designed as 3:1 for maximum radiation exposure on the glass window at any time in a day. It helped in eliminating the need for azimuthal tracking of the cooker, which is essential for a simple hot box solar cooker. The solar cooker was capable of boiling 10 kg animal feed per day, sufficient for four cattle heads, with efficiency of 26.4 per cent. The thermal performance of the animal feed solar cooker through stagnation and water boiling tests performed during April, 2016 indicated the First Figure of Merit (F1), Second Figure of Merit (F2) and standardized cooking power (Ps) to be 0.089 m2.Â°C.W-1, 0.288 J.W-1.Â°C-1 and 27.40 W, respectively. It indicates that the developed cooker falls under category â€œBâ€ of BIS standard, but sufficient for cooking of animal feed once a day.